Disinsediare l’io. Geografie di Antonella Anedda ovvero essere altro(ve) - Donati, Riccardo (L'ospite ingrato, 2022)
This essay concerns the prose book Geografie (2021), written by the Italian poet Antonella Anedda. The study of Geografie’s underlying mechanisms (focusing on the author’s ideas, style, rhetoric) allows to highlight the characteristics and importance of this text, both with respect to Anedda’s work (across a thirty-year long career) and in relation to some crucial issues in our present social, political and cultural debate.